2021
DOI: 10.1111/aas.13795
|View full text |Cite
|
Sign up to set email alerts
|

Higher vs lower doses of dexamethasone in patients with COVID‐19 and severe hypoxia (COVID STEROID 2) trial: Protocol and statistical analysis plan

Abstract: Background The coronavirus disease 2019 (COVID‐19) pandemic has resulted in millions of deaths and overburdened healthcare systems worldwide. Systemic low‐dose corticosteroids have proven clinical benefit in patients with severe COVID‐19. Higher doses of corticosteroids are used in other inflammatory lung diseases and may offer additional clinical benefits in COVID‐19. At present, the balance between benefits and harms of higher vs. lower doses of corticosteroids for patients with COVID‐19 is uncl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 23 publications
0
46
0
Order By: Relevance
“…17 The COVID STEROID trial was paused following the preliminary results from the RECOVERY trial and afterwards terminated after publication of the WHO meta-analysis. 3,4 Additional details on the COVID STEROID 2 trial including detailed variable definitions are available in the primary protocol 9 and on the trial website (www.cric.nu/covid -stero id-2).…”
Section: Study Design and Conductmentioning
confidence: 99%
See 4 more Smart Citations
“…17 The COVID STEROID trial was paused following the preliminary results from the RECOVERY trial and afterwards terminated after publication of the WHO meta-analysis. 3,4 Additional details on the COVID STEROID 2 trial including detailed variable definitions are available in the primary protocol 9 and on the trial website (www.cric.nu/covid -stero id-2).…”
Section: Study Design and Conductmentioning
confidence: 99%
“…The primary trial protocol 9 was prepared according to the Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) statement 18 ; this secondary study protocol was prepared in accordance with the STrengthening the Reporting of OBservational studies in Epidemiology (STROBE) statement 19 (completed checklist included in the supplement) with the Bayesian analyses specified in accordance with the Reporting Of Bayes Used in clinical STudies (ROBUST) guideline. 20 The primary trial results will be reported in accordance with the Consolidated Standards of Reporting Trials (CONSORT) statement, 21 and the results from this secondary analysis will be reported in accordance with the STROBE statement and the ROBUST guideline regardless of the results.…”
Section: Approvals and Reportingmentioning
confidence: 99%
See 3 more Smart Citations